English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

10 ^ (x + 3) = 6 ^ (2x)

Could someone please help me with this? I keep having trouble when there is a variable on both sides.
I get as far as this
(x + 3)log(10) = (2x)log(6)
xlog(10) + 3log(10) = 2xlog(6) Can't get rid of 2x

2006-10-18 06:59:27 · 3 answers · asked by ctjarig 1 in Science & Mathematics Mathematics

3 answers

you already are up to
xlog(10) + 3log(10) = 2xlog(6)

rearranging, we get
x(log10-2log6) = -3 log10

i assume log10=1 (ie.base 10)

so x(1-2log6) = -3

x = 3 / (2log6-1)

2006-10-18 08:01:21 · answer #1 · answered by m s 3 · 1 0

log 10 = 1 so,
xlog(10) + 3log(10) = 2xlog(6)
x + 3 = 2xlog(6)
3= 2xlog(6) -x
3= x(2log(6) -1)
x= 3/2log(6)

2006-10-18 07:45:20 · answer #2 · answered by Anonymous · 0 0

(x+3) / (2x)=log(6) / log(10)

The right side is a constant and the rest should be algebra you already know.

2006-10-18 08:16:00 · answer #3 · answered by rhino9joe 5 · 0 0

fedest.com, questions and answers